A Survey on Indoor Radon Concentration in Thammasat University Rangsit Campus: A pilot study - Phantawong, Kochakorn; sukeaw, Thapanat; surakumhang, Tassamon (Thammasat University Hospital Journal Online, 2025)
Background: Radon is a natural gas that results from uranium decay. Radon is mostly found at high levels near uranium mining areas, geological formations such as granite, and hot springs, where water from underground aquifers rises to the surface. These areas are considered open spaces. Closed areas, such as residential buildings, often accumulate radon gas in the soil, rock, and sand used in construction. Prolonged exposure to high levels of radon gas can affect health by increasing the risk of lung cancer. Objective: To measure and compare the concentration of radon gas in each building located within Thammasat University, Rangsit Center, Pathum Thani Province. Materials and methods: CR-39 plastic film-type radon measurement plates were installed on the first floor of 22 buildings within Thammasat University. The plates were installed for 40 days, after which the radon concentration was analyzed using the nuclear track etching method. Result: The buildings with the highest and lowest radon gas concentrations were the area of the pillars in front of the Social Science Building 2 (SC2) and the fire escape, 1st floor of the Ratchasuda Building, with values of 873.35 ± 9.35 Bq/m3 and 6.35 ± 0.67 Bq/m3, respectively. In the dormitory zone, the average radon gas concentrations in Dormitories A, B, C, and F ranged from 39.38 ± 49.73 to 82.47 ± 114.28 Bq/m3. In the classroom zone, the Piyachart1 Building, Piyachart2 Building, Rajchuda Building, and Social Sciences Building 1-3 had an average value ranging from 16.41 ± 12.01 to 351.46 ± 455.00 Bq/m3. Conclusion: Areas with radon gas concentrations exceeding 148 Bq/m3 were found in the dormitory zone, which has relatively low air circulation and inadequate ventilation. In Social Science Buildings 2 and 3, some areas showed high radon gas concentration levels, particularly in enclosed spaces, and some areas had abnormally high values that should be re-measured.